Ubiquitomics: An Overview and Future - George Vere; Rachel Kealy; Benedikt M. Kessler; Adan Pinto-Fernandez (Biomolecules, 2020)
Covalent attachment of ubiquitin, a small globular polypeptide, to protein substrates is a key post-translational modification that determines the fate, function, and turnover of most cellular proteins. Ubiquitin modification exists as mono- or polyubiquitin chains involving multiple ways how ubiquitin C-termini are connected to lysine, perhaps other amino acid side chains, and N-termini of proteins, often including branching of the ubiquitin chains. Understanding this enormous complexity in protein ubiquitination, the so-called ‘ubiquitin code’, in combination with the <semantics><mstyle displaystyle="false" scriptlevel="1">∼</mstyle></semantics>1000 enzymes involved in controlling ubiquitin recognition, conjugation, and deconjugation, calls for novel developments in analytical techniques. Here, we review different headways in the field mainly driven by mass spectrometry and chemical biology, referred to as “ubiquitomics”, aiming to understand this system’s biological diversity.